Sediment-Associated Phytoplankton Release From the Seafloor in Response to Wind-Induced Barotropic Currents in the Bering Strait - Abe, Hiroto; Sampei, Makoto; Hirawake, Toru; Waga, Hisatomo; Nishino, Shigeto; Ooki, Atsushi (Frontiers in Marine Science, 2019)
Bering Strait is the single gateway between the Arctic and Pacific Oceans, and has localized strong currents, which can reach up to 100 cm s−1. Although massive spring phytoplankton blooms and the subsequent production of particulate organic matter that sinks to the seafloor are observed in the surrounding regions of the Bering Strait, the impact of the locally strong current on the horizontal and vertical transport of the particles remains unclear. Therefore, we conducted year-round mooring measurements from 2016 to 2017 by focusing on near-bottom processes associated with ocean currents. Our time-series analysis showed that high-turbidity events, triggered by strong barotropic currents, occurred near the seafloor in all seasons. Consequently, the fluorescence sensor detected highly concentrated chlorophyll a in the resuspended sediment; however, the amount of chlorophyll a release was seasonal, with large and small amounts being released during the warm and cold seasons, respectively. The small amounts of chlorophyll a may be attributed to small amounts of phytoplankton in the sediment owing to less input of fresh phytoplankton from the overlaying water column and organic matter decomposition in the sediments under no-light conditions. The barotropic currents were modulated by surface winds associated with an intercontinental atmospheric pattern having a 5000-km spatial scale on a timescale of 6 days. The locally strong ocean current in the Bering Strait, driving the upward transport of sediment and the subsequent horizontal transport, may play a vital role in supplying particulate organic matter/phytoplankton/nutrients to the downstream region of the southern Chukchi Sea where the formation of biological hotspots is reported.